Eocene out-of-India dispersal of Asian dipterocarps - Dutta, S.; Tripathi, S.; Mallick, M.; Mathews, R.; Greenwood, Paul; Rao, M.; Summons, R. (2011)
The Dipterocarpaceae, a well known and economically important family of trees of the tropical rain forests of Asia, comprise over 470 species. These angiosperm trees contribute to 30% of the total area in typical lowland evergreen forests in Southeast Asia. Despite their remarkable diversity and regional ecological dominance, the origins and phytogeographical evolution of the family are poorly understood. The earliest dipterocarp fossils recorded in SE Asia come from Oligocene (34-23. Ma) sediments of Borneo. Here, we report an occurrence of Asian dipterocarps from approximately 53. Ma old sediments from western India based on fossil resin chemistry and palynological data. An important implication of our finding is that Asian dipterocarps must have originated in Gondwana and dispersed from India into Asia once the land connection between the Indian and Asian plate was well established during the middle Eocene (49-41. Ma). Moreover, the present study supports the hypothesis which suggests that many angiosperms did not originate in the SE Asian region, but dispersed into the area from western Gondwanaland. © 2011 Elsevier B.V.